THE DECLINE OF THE HARAPPAN CIVILIZATION: AN ANALYSIS OF ENVIRONMENTAL AND CLIMATIC FACTORS - Jayswal, Bablu Kumar (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
This research paper analyzes the gradual decline of the Indus Valley Civilization (IVC), one of the most advanced urban-centered civilizations of the ancient world, and the crucial role of climate change in its demise. For a long time, it was believed that the civilization ended due to foreign invasions or sudden floods, but modern archaeological evidence and paleoclimate data tell a different story. The main focus of this study is the weakening of the South-West Monsoon around 1900 BCE and the resulting prolonged aridity. This paper examines how the changes in monsoon patterns affected river levels, particularly impacting the Ghaggar-Hakra (Saraswati) river system. The water scarcity not only eliminated agricultural surpluses but also disrupted the food supply chains of the large cities. In conclusion, this research establishes that the decline of the Indus Valley Civilization was not a sudden event but a cultural transformation, where adverse climatic conditions forced people to abandon organized urban life and migrate eastward (to the Ganges plains) and southward in the form of smaller rural communities. This study also offers a historical warning and lesson for the current global climate crisis.